Spatial structure of vegetation in a small charophyte dominated lake - Pukacz, Andrzej; Pełechaty, Mariusz (Biodiversity: Research and Conservation, 2013)
The aim of the paper was to recognize the current spatial structure and organization of vegetation and the diversity of charophytes on an ecosystem scale of a small, outflow Lake Jasne (Western Poland). The lake is characterized by limited anthropogenic pressure and forested catchment basin. The study was performed in the vegetative season 2010. The vegetation was studied along transect, using the mid-European Braun-Blanquet method of phytosociological relevés. Additionally, basic physical-chemical parameters were measured, to characterize habitat conditions of the lake. The results of physical-chemical analyses evidenced high water quality, and obtained parameter values were typical for mesotrophy. The vegetation survey revealed that almost 70% of the lake’s bottom was overgrown by vegetation. The transects documented the structure of phytolittoral typical for chara-lake and the spatial dominance of charophytes in the studied lake (charophyte meadows reached up to 64% of the phytolittoral area). Charophytes were also defining the maximum depth extent of vegetation in Lake Jasne, reaching 5.6 m. As many as 10 charophyte species were stated: Chara virgata, Ch. aspera, Ch. filiformis, Ch. globularis, Ch. intermedia, Ch. polyacantha, Ch. rudis, Ch. tomentosa, Nitella flexilis and Nitellopsis obtusa, out of which 7 build their own communities. The large number of species (10 of 35 identified so far in Poland) and communities (7 of 30 identified in Poland), as well as their share in phytolittoral, define Lake Jasne as a valuable refuge of European natural habitat, code 3140.